PERILAKU INOVATIF KEPALA SEKOLAH DALAM PENGELOLAAN SARANA ICT SMP - Anita Anita; Rambat Nur Sasongko; Turdjai Turdjai (Manajer Pendididikan, 2017)
The purpose of this study is to describe the school principal innovativeness in ICT Facilities and Infrastructure management at Junior High School Number 2 Lubuklinggau. This study uses descriptive qualitative method. The subjects of this study are the school principal, the vice of the school principals, the teacher, the staff, and the students. The data were collected by means of interview, observation, and documentation and analyzed by using qualitative descriptive technique as proposed by Miles and Huberman. The result of this study shows: (1) The planning of ICT facilities and infrastructure has conformed with the school vision and mission (2) The school principal cooperated with the vice school principal in ICT facilities and infrastructure provision (3) The process of ICT facilities inventory is only done by the vice school principal without the school principal intervention (4) The school principal has utilized the ICT facilities base of its function (5) The school principal is not innovative in term of ICT facilities and infrastructure storage system, and (6) The school principal is not innovative in ICT facilities and infrastructure maintenance system.